Design and Implementation of an Intelligent Chicken Egg Incubation System Using Light and Temperature Sensors Based on Arduino UNO R3 - Dafa Raihan Ranindra Putra; Hafiz Nurhan Putra; Jessica Feodora Baeha; Muhammad Wahid Adhi Prakosa; Purnawarman Musa (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This research aimed to develop an intelligent chicken egg incubation system that maintained stable environmental conditions using light and temperature sensors controlled by an Arduino UNO R3. The system addressed the problem of unstable temperature and humidity in traditional manual hatching, which often resulted in low hatchability rates. The proposed incubator integrated a DHT22 sensor, LDR, keypad, relay module, servo motors, and a microcontroller that automatically regulated heating, ventilation, and egg-turning mechanisms. The prototype was tested through several stages, including sensor responsiveness, actuator performance, security verification, and a comparative incubation experiment. The system was then evaluated using two groups of eggs: an experimental group incubated using the automatic system and a control group incubated manually without environmental regulation. Test results showed that all system components operated consistently, with temperature and humidity maintained within the ideal range for incubation. Embryos in the experimental group exhibited normal growth until hatching, while all embryos in the control group failed to develop due to extreme environmental fluctuations. These findings demonstrated that the automated incubator successfully created a controlled and stable environment capable of supporting healthy embryo development.